Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Chronic Kidney Disease (CKD) Di Ruang Rawat Inap Muzdalifah Rumah Sakit Aisyiyah - Ratu Amelia; Mike Asmaria; Hilma Yessi; Debby Silvia (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Chronic Kidney Disease (CKD) is a progressive and irreversible impairment of kidney function. Globally, CKD is estimated to affect approximately 843.6 million individuals worldwide, with mortality rates continuing to increase annually, making it the 12th leading cause of death globally. In Indonesia, the main risk factors for CKD are hypertension (34.1%), diabetes mellitus (8.5%), and obesity (21.8%). Meanwhile, in the Muzdalifah Inpatient Ward of Aisyiyah Pariaman Hospital, the number of CKD cases increased from 61 cases in 2023 to 79 cases in 2025. The purpose of this study was to implement Medical-Surgical Nursing Care for a patient with CKD using a case study method and anamnesis approach. This study was conducted in the Muzdalifah Inpatient Ward from February 18 to 22, 2026.The assessment findings in Mrs. M revealed symptoms including lower back pain with a pain scale of 6, lower extremity edema, shortness of breath, nausea, generalized weakness, and decreased urine output. The nursing problems identified were impaired gas exchange, hypervolemia, ineffective peripheral tissue perfusion, acute pain, unstable blood glucose levels, and risk for decreased cardiac output. Nursing interventions provided included respiratory monitoring, hypervolemia management, circulatory care, pain management, hyperglycemia management, cardiac care, and health education. Evaluation results showed that impaired gas exchange and acute pain were resolved on the third day, hypervolemia and ineffective peripheral tissue perfusion were resolved on the fifth day, unstable blood glucose levels were partially resolved, and no signs of decreased cardiac output occurred during the hospitalization period.